Common mycorrhizal network: the predominant socialist and capitalist responses of possible plant–plant and plant–microbe interactions for sustainable agriculture - Ullah, Asad; Gao, Danmei; Wu, Fengzhi (Frontiers in Microbiology, 2024)
Plants engage in a variety of interactions, including sharing nutrients through common mycorrhizal networks (CMNs) which are facilitated by arbuscular mycorrhizal fungi (AMF). These networks can promote the establishment, growth, and distribution of limited nutrients that are important for plant growth, which in turn benefits the entire network of plants. Interactions between plants and microbes in the rhizosphere are complex, and can either be socialist or capitalist in nature and the knowledge of these interactions is equally important for the progress of sustainable agricultural practice. In the socialist network, resources are distributed more evenly providing benefits for all connected plants such as symbiosis. E.g., direct or indirect transfer of nutrients to plants, direct stimulation of growth through phytohormones, antagonism towards pathogenic microorganisms and mitigation of stresses. For the capitalist network, AMF would be privately controlled for the profit of certain group of plants hence increasing competition between connected plants. Such as plant interactions invading by microbes act as saprophytic and cause necrotrophy in the colonizing plants. In the first case, excess of the nutritional resources may donate to the receiver plants by a direct transfer. While in the second case, unequal distribution of the resources occurs which certainly favor individual group and increase competition between interactions. This largely depends on which of these responses are predominant (“socialist” or “capitalist”) in the moment plants are connected. Therefore, some plant species might benefit from CMNs more than others, depending on the fungal species and plant species involved in the association. Nevertheless, benefits and disadvantages from the interactions between the connected plants are hard to distinguish in nature, once most of the plants are colonized simultaneously by multiple fungal species, each one with its own cost-benefits. Classifying plant-microbial interactions based on their habitat specificity, such as their presence on leaf surfaces (phyllospheric), within plant tissues (endophytic), on root surfaces (rhizospheric), or as surface-dwelling organisms (epiphytic), helps to highlight the dense and intricate connections between plants and microbes that occur both above and below ground. In these complex relationships, microbes often engage in mutualistic interactions, where both parties derive mutual benefits,